FLANKING STRUCTURES - Passchier C.W. (My University, 2001)
Flanking structures are deflections of planar or linear fabric elements in a rock alongside a cross-cutting object such as a vein, fracture or burrow. Flanking structures are divided into flanking-folds and flanking shear-bands. Both structures can develop by a range of mechanisms including intrusion or in situ formation of veins that bisects existing fold trains or shear-bands along the axis of the structure; flow partitioning alongside an active fault in a ductilely deforming rock; passive rotation of a vein with attached narrow rim of wall rock formed by alteration of the wall rock during intrusion of the vein; development of a shear zone in or along a pre-existing vein; and passive amplification of small deflections alongside a vein or burrow. Flanking structures can be used to establish a sequence of deformation and intrusion or partial melting, and some types of flanking structures can be used as shear sense indicators or to determine finite strain.